Optimization and validation of a liquid chromatography tandem mass spectrometry (LC/MSn) method for analysis of corticosteroids in bovine liver: evaluation of Keyhole Limpet beta-glucuronidase/sulfatase enzyme extract. - Croes,K.; Goeyens,L.; Baeyens,W.; Joris Van Loco; Impens,S. (Journal of Chromatography B: Analytical Technologies in the Biomedical and Life Sciences, 2009)
A liquid chromatography tandem mass spectrometry (LC/MS(n)) method for the determination of 12 corticosteroids in bovine liver has been optimized and validated in accordance with the European Commission Decision 2002/657/EC. A bovine liver sample was deconjugated with beta-glucuronidase/sulfatase enzyme, extracted with diethyl ether and further cleaned up with Solid Phase Extraction (SPE) before analysis with LC/MS(n). Two different enzyme extracts (originating from Helix Pomatia and Keyhole Limpet) and three SPE elution solvents (ethyl acetate, acetonitrile and methanol) were compared during the optimization. Helix Pomatia is generally known as the enzyme most being used for enzymatic hydrolysis purposes. Nevertheless, when detecting corticosteroids in the low microg kg(-1) concentration range, the Helix Pomatia extract may lead to interferences in the final LC/MS(n) chromatogram. When using the Keyhole Limpet enzyme extract, no interferences were observed and therefore, this extract was the best choice for enzymatic hydrolysis tested in this case. Ethyl acetate was used as elution solvent during the validation procedure since SPE elution with acetonitrile resulted in higher chromatographic backgrounds, while elution with methanol showed less reproducible results. Validation of the optimized method was carried out for 10 of the 12 corticosteroids, giving mean recoveries between 91 and 109%, and repeatability and reproducibility coefficients of respectively maximum 13.7 and 18.0%. The working ranges for the linear calibration curves were 5-20 microg kg(-1) for prednisolone, methylprednisolone and prednisone and 0.5-4 microg kg(-1) for the other compounds (coefficients of determination R(2)> or =0.97). Specificity, decision limit (CCalpha) and detection capability (CCbeta) were for all compounds within the EC specified limits.
Keywords: ALL; analysis; AS; Calibration; Case; chromatography; Commission Decision 2002/657/EC; Decision; detection; Detection capability; European; European Commission; EVALUATION; Hydrolysis; Interference; IS; Lead; Less; liquid chromatography; Liver; Mass; Mass Spectrometry; method; observed; RANGE; Reproducibility; result; results; Sample; Solvents; Tandem Mass Spectrometry; VALIDATION